“T-CoRe”: a new instrument for studies on Technological Pedagogical Content Knowledge and for technological teacher education - Percia Paiva Barbosa; Gabriela dos Santos Brito; Suzana Ursi (Revista de Ensino de Ciências e Matemática, 2025)
Competencies related to the use of technologies are essential for today’s citizens, justifying their implementation in educational environments. However, teacher education is crucial for effective learning with these resources. Thus, research on teachers’ Knowledge Bases, including Technological Pedagogical Content Knowledge, becomes highly relevant. This article presents “T-CoRe”, an instrument designed to support teachers’ technological education and facilitate research in this field. Inspired by Loughran and collaborators, “T-CoRe” consists of eight questions regarding using technological resources in teaching, enabling access to teachers’ Knowledge Bases, particularly their technological knowledge. The instrument was tested with future Biology teachers, revealing promising aspects of “T-CoRe” for research purposes. The results also emphasize the instrument’s capacity to identify gaps in Knowledge Bases throughout teacher education.